P-OGC83 The Impact of Covid-19 on Malignant Upper GI Operations in England During 2020. (16th December 2021) - Sandland-Taylor, Laura; Jenkins, Barbara; Beckingham, Ian
Abstract: Background: Due to the Covid-19 pandemic and the overwhelming number of patients requiring ITU due to serious Covid-19 infections, trusts throughout England reduced their operation numbers to reduce the burden on secondary care services. Whilst efforts were made to preserve cancer services in England, the Covid-19 burden still significantly impacted the provision of oesophagectomies and gastrectomies. The following research aims to look at the true impact of Covid-19 on operation numbers in England and compare these to the Covid-19 burden.  Methods: Data relating to operation numbers was taken from The Surgical Workload Outcomes Audit (SWORD) database. The SWORD database was interrogated for the years 2017 – 2020. A mean number of operations was calculated using the 2017-2019 data and compared to data from 2020. Operations performed and other demographic data  was analysed regionally and compared to Covid-19 deaths throughout England. Covid-19 data was obtained from the national government dashboards.  Results: Results showed that there was a significant reduction in the number of operations performed in 2020 due to the Covid-19 pandemic. This was closely correlated with Covid deaths throughout England. Variations between centres were present throughout the UK, however the overall trend reflected more than a 40% reduction in gastrectomies and more than a 30% reduction in oesophagectomies, which equated to 1018 less gastrectomies and 490 less oesophagectomies performed in 2020. There was significant variation between centres, the impact on individual centres and oesophagectomy rates ranged from -0.8% reduction to a 100% reduction in operations carried out in 2020. Gastrectomies was similarly affected, varying between a 2.7% and 89.5% reduction in operations carried out in 2020.  Conclusions: Overall, despite efforts to preserve procedures, particularly for malignant disease, there was significant fall in operations performed throughout 2020. As a consequence of this, it is likely that patients requiring life saving or life extending operations did not receive their treatment. The data suggests that overall gastrectomies were worse hit than oesophagectomies across England. Variances in performance across the UK should be further analysed to allow better planning and resource allocation for future waves or future pandemics.